The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/01.tp.0000277672.02783.33
|View full text |Cite
|
Sign up to set email alerts
|

Asialoerythropoietin Has Strong Renoprotective Effects Against Ischemia-Reperfusion Injury in a Murine Model

Abstract: EPO and asialoEPO attenuated renal dysfunction caused by I/R in mouse kidney at the same level, but only asialoEPO improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
3
29
0
1
Order By: Relevance
“…For example, both asialoEPO and a small peptide mimic of EPO (pyroglutamate helix B surface peptide [pHBSP] [62]) have plasma half-lives of only ~2 min. Yet both are highly effective in preventing injury in a wide range of neurological and other acute injuries after only a single parenteral dose (32,(64)(65)(66).…”
Section: Development Of Tissue-protective Receptor-specific Ligandsmentioning
confidence: 99%
“…For example, both asialoEPO and a small peptide mimic of EPO (pyroglutamate helix B surface peptide [pHBSP] [62]) have plasma half-lives of only ~2 min. Yet both are highly effective in preventing injury in a wide range of neurological and other acute injuries after only a single parenteral dose (32,(64)(65)(66).…”
Section: Development Of Tissue-protective Receptor-specific Ligandsmentioning
confidence: 99%
“…This concept was further validated in other tissues, including kidneys. 12 Administration of asialoEPO also protected against ischemia reperfusion injury in the heart, possibly through mechanisms involving inhibition of apoptosis. 13 In addition, we recently demonstrated that asialoEPO attenuates nephrectomy induced left ventricular remodeling and dysfunction without increasing hemoglobin levels.…”
mentioning
confidence: 99%
“…46 In fact, the action of Epo does not seem to be limited to controlling proliferation and differentiation of erythroid cells. It overcomes the effect on the hematopoietic system [47][48][49] and functional receptors for Epo have been found in both nonerythroid blood cell lines and a variety of nonhematopoietic cells, suggesting new roles in nonhematopoietic tissues. These include brain (astrocytes and neurons, both provided with specific Epo-R), cardiovascular system (cardiomyocytes, endothelium, and vascular smooth muscle), spinal cord, reproductive organs, skeletal muscle, retina, gastrointestinal tract (gut and pancreas), and lung.…”
Section: Extra-erythropoietic Actions Of Epo: Opening New Frontiersmentioning
confidence: 98%